2019
DOI: 10.1002/smll.201905446
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Powered Shape‐Transformable Liquid Metal Micromotors

Abstract: The creation of micromotors that can convert stored energy to autonomous movement would be of great value in various applications, ranging from chemical sensing to precision water-quality screening and from cleaning clogged arteries to repairing microscopic cracks. Many of micromotors, based on different propulsion mechanisms (e.g., magnetic fields, ultrasound filed, chemical fuels, light, and bubble propulsion), [1][2][3][4][5][6][7][8][9] have been designed and fabricated over the past decade. Generally, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 44 publications
1
53
0
Order By: Relevance
“…LMMMs are generally in the shape of spheres [45], rods [46], and rice ( Figure 2A) [47], which is determined by fabrication methods and parameters [46,48]. There are three common methods to prepare MCLMTs: Sonication [25], transfer printing [49], and pressurefilter-template [9] methods. The former one can produce LMMMs in the sphere, rod, and rice shape by varying parameters.…”
Section: Shapementioning
confidence: 99%
See 2 more Smart Citations
“…LMMMs are generally in the shape of spheres [45], rods [46], and rice ( Figure 2A) [47], which is determined by fabrication methods and parameters [46,48]. There are three common methods to prepare MCLMTs: Sonication [25], transfer printing [49], and pressurefilter-template [9] methods. The former one can produce LMMMs in the sphere, rod, and rice shape by varying parameters.…”
Section: Shapementioning
confidence: 99%
“…By contrast, spheres can be hardly propelled by these two fields, because the symmetry lengths of diameters cannot produce enough pressure difference. For MCLMTs motivated by magnetic fields, special designs such as helical tails and dumbbell-like shapes are required [49]. Besides, the function of LMNPs can also be influenced by their shape.…”
Section: Shapementioning
confidence: 99%
See 1 more Smart Citation
“…They are often used to actuate helical robots, one of the most widely used designs of microrobots or nanorobots whose actuation is achieved by the induction of rolling, corkscrew, and spin-top motions [ [42] , [43] , [44] ]. It has been found in the literature that the magnetic particle aggregates and some other interesting structures can be manipulated by rotating magnetic fields as well [ [45] , [46] , [47] , [48] , [49] , [50] ].…”
Section: Recent Advancements Of the Design Of Magnetic Small-scale Romentioning
confidence: 99%
“…Another interesting research about magnetic micromotors was reported by Liu et al recently. [58] In this study, they presented a design and fabrication of shape-transformable liquid metal micromotors using The magnetic field acting on the micromotor could make the motor wobbles rapidly, which immediately broke the symmetry of pressure distribution in fluid and then led to the motion of micromotors. Furthermore, due to the oxide layer of EGaIn was broken by local heat during the conversion from magnetic energy, the liquid metal micromotors could undergo a morphological transformation.…”
Section: Magnetically Propelled Micro/nanomotorsmentioning
confidence: 99%